A contribution to the study of the German treasury bills market - Leão, E. R.; Lagoa, S. C. (Cogent Economics and Finance, 2015)
We study the yields in the German treasury bills market. We take a detailed look at the yield banks require to buy treasury bills in the primary market, and we also examine the yield households and nonbank firms demand to buy these bills in the secondary market. We use data from real world tenders to show that the bids set by banks are in accordance with the predictions of our theoretical framework. In particular, we show that current monetary policy and the market's expectations regarding the future path of monetary policy can be used to define an interval in which the bids from banks lie. Our theoretical predictions for the secondary market also match the data.